Optimalisasi Peran Kader Posyandu dan Tim Pendamping Keluarga Sebagai Konselor Pemberian Makanan Bayi dan Anak di Desa Cabeyan, Sukoharjo. - Firmansyah; Puan Ayu Safir Agusta; Kharisma Kusuma Wardani (BALE LITERASI, 2025)
Reducing the prevalence of stunting is one of the goals in Indonesia's development, the 2025 Global Nutrition Targets and is included in the indicators in the Sustainable Development Goals (SDGs). However, one in three children in Indonesia suffers from stunting. The government has made various efforts to achieve this goal, namely by referring to the recommendations of the Lancet 2013 which include sensitive and specific nutritional interventions. To support these efforts, the proposer prepared a proposal to assist in accelerating stunting reduction in Cabeyan Village with nutrition education activities on feeding infants and children (PMBA). PMBA is an activity that includes exclusive breastfeeding socialization, how to process local food in Cabeyan Village, Bendosari, Sukoharjo such as practicing snack cooking demonstrations that can be used as MP Breast Milk and PMT recovery for stunted toddlers. In addition, the food products produced can also be sold to improve the economy in the village. The PMBA program will be carried out at each posyandu in Cabeyan Village which adjusts to the routine schedule of the Posyandu for toddlers. Community Service uses the lecture method, namely providing PMBA counseling to posyandu cadres and family companion cadres totaling 24 people. Furthermore, the target of this activity will be a peer-educator to the community in Cabeyan Village regarding the practice of feeding infants and children. The success indicator of this activity is that it can be followed by 100% of posyandu cadres and family companions who can then provide insight into improving the knowledge of mothers under five and the community in Cabeyan Village by utilizing local food. In addition, there was an increase in target knowledge of more than 70% at the time of knowledge evaluation